Elastodynamic response of cracked orthotropic strip under impact loading - Das S. (My University, 2025)
The paper presents the elastodynamic response of an infinite orthotropic strip of finite width containing a central crack opened by suddenly applied stresses. Integral transforms are employed to reduce the transient problem to the solution of a pair of dual integral equations in the Laplace transform plane solved by iterations in the low frequency case. Analytic expressions for the dynamic stress intensity factors are obtained. Numerical results for two particular materials are given. The influence of different orthotropic constants on the magnitude of the overshoots in the stress intensity factors K1(t) and K2(t) are found. © Springer Science+Business Media B.V. 2009.